Intelligent autonomous vehicles in digital supply chains: From conceptualisation, to simulation modelling, to real-world operations. Issue 3 (27th June 2019) - Tsolakis, Naoum; Bechtsis, Dimitrios; Srai, Jagjit Singh
Abstract : Purpose: The purpose of this paper is twofold: first, to discuss key challenges associated with the use of either simulation or real-world application of intelligent autonomous vehicles (IAVs) in supply network operations; and second, to provide a theoretical and empirical evidence-based methodological framework that supports the integrated application of conceptualisation, simulation, emulation and physical application of IAVs for the effective design of digital supply networks. Design/methodology/approach: First, this study performs a critical review of the extant literature to identify major benefits and shortcomings related to the use of either simulation modelling or real-word application of physical IAVs. Second, commercial and bespoke software applications, along with a three-dimensional validation and verification emulation tool, are developed to evaluate an IAV's operations in a conceptual warehouse. Third, a commercial depth-sensor is used as a test bed in a physical setting. Findings: The results demonstrate that conceptual and simulation modelling should be initially used to explore alternative supply chain operations in terms of ideal performance while emulation tools and real-world IAV test beds are eminent in validating preferred digital supply chain design options. Research limitations/implications: The provided analysis framework was developed using literature evidence along with experimental work and research experience, without consulting any industry experts. In addition, this study was developed based on the application of a single physical device application as a test bed and, thus, the authors should further progress with the testing of a physical IAV in an industrial warehouse. Practical implications: The study provides bespoke simulation modelling and emulation tools that can be useful for supply chain practitioners in effectively designing network operations. Originality/value: This work contributes in the operations management field by providing both a multi-stage methodological framework and a practical "toolbox" for the proactive assessment and incorporation of IAVs in supply network operations.